Pengaruh Motivasi Dan Lingkungan Kerja Non Fisik Terhadap Kinerja Karyawan Pada PT Indomarco Prismatama Cabang Parung Bogor Area Bsd Tangerang Selatan - Dewi Rahmamita; Ahmad Syukri (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract - The purpose of this study was to see the Influence of Work Motivation and Non-Physical Work Environment on Employee Performance of PT. Indomarco Prismatama Parung Bogor branch, BSD Tangerang Selatan area. This research method uses a quantitative method with population and a sample of 55 respondents, data analysis techniques used are: validity test, reliability test, normality test, multiconearity test, autocorrelation test, heteroscedasticity test, simple linear regression test, multiple linear regression test, simple correlation coefficient test, multiple correlation coefficient test, determination coefficient analysis test, t test and f test. Based on the results of data analysis, the calculated t value> t table or (7.747> 2.006). This is also reinforced by the ρ value <Sig. 0.05 or (0.000 <0.05) it can be concluded that there is an influence between motivation and the work environment. Non-Physical Work Environment has a significant effect on the acquisition of regression equation values ​​Based on the test results, the linear regression equation value Y = 18.269 + 0.571, the correlation coefficient is 0.720, meaning that the two variables have a strong relationship. The determination value or the amount of contribution of influence is 51.9%, while the rest is (100 - 51.9% = 48.1%), influenced by other factors. Hypothesis testing obtained a calculated t value> t table or (7.55> 2.006). This is also reinforced by the ρ value <Sig. 0.05 or (0.000 <0.05). the results of the calculated F test> F table value or (36.649> 8.53), this is also reinforced by the ρ value <Sig. 0.05 or (0.000 <0.05). Thus, H0 is rejected, and H3 is accepted, meaning that there is a positive and significant influence simultaneously between the influence of Motivation (X1) and Non-physical Work Environment (X2) on Employee Performance (Y) at PT. Indomarco Prismatama Parung Bogor Branch BSD Area South Tangerang.